Influence of transport air pollutants on climate change in EU: case of Lithuania - Kęstutis Peleckis; Valentina Peleckienė; Bahman Peyravi (Business: Theory and Practice)
The purpose of the research paper is to observe and analyse how the motorization rate of EU countries influence climate change during the last decades in terms of inventory of emissions of air pollutants from transport, giving an example of Lithuania. Passenger cars are a major polluter, accounting for 61% of total CO2 emissions from EU road transport. EU approved directions to transitioning to fossil-free transport and reducing car use in future to make the European Union carbon neutral by 2050. Research methodology is statistical analysis of motorization rate growth and air pollution in the EU countries during the period of 2014–2024. In the research paper the quantitative analysis and comparison method are applied. Findings: research paper shows that in the EU countries motorization rate is growing very fast. However the consequences of this vary from country to country. Significant disparities arise from the age of the vehicles, the type of fuel utilized, and the turnover rate of passenger cars, resulting in the current fleet not achieving an adequate decrease in CO2 emissions. This research examines the correlation between motorization levels and CO2 emissions across several EU countries over recent decades and offers potential solutions to this issue.